Boosting freshwater fish conservation with high‐resolution distribution mapping across a large territory - Juan Tao; Chengzhi Ding; Jinnan Chen; Liuyong Ding; Sébastien Brosse; Jani Heino; Virgilio Hermoso; Ruidong Wu; Ziwang Wang; Jiaxin Hu; Rongxiao Che; Xiaowei Jin; et al. (Conservation Biology, 2023)
The lack of high‐resolution distribution maps for freshwater species across large extents fundamentally challenges biodiversity conservation worldwide. We devised a simple framework to delineate the distributions of freshwater fishes in a high‐resolution drainage map based on stacked species distribution models and expert information. We applied this framework to the entire Chinese freshwater fish fauna (>1600 species) to examine high‐resolution biodiversity patterns and reveal potential conflicts between freshwater biodiversity and anthropogenic disturbances. The correlations between spatial patterns of biodiversity facets (species richness, endemicity, and phylogenetic diversity) were all significant ( r = 0.43–0.98, p